IMPLEMENTING PAI CURRICULUM IN SDQT NURUL ISLAM - Arifudin, Yadi Fahmi; Rochmah, Elfina Nur; Wulandari, Dewi (Journal Analytica Islamica, 2024)
The Islamic education curriculum aims to instill faith in the minds and hearts of the younger generation, restore morals, and awaken spiritual consciousness. The curriculum also aims for continuous acquisition of knowledge, integration of knowledge and work, faith and morality, as well as the application of theoretical practices in life. This study aims to understand the development and implementation of the Islamic Religious Education curriculum at SDQT Nurul Islam Karawang. This research uses field research with a qualitative approach. Data collection techniques include interviews, observations, and documentation. The results of this study indicate that the Islamic Religious Education curriculum at SDQT Nurul Islam Karawang is running smoothly according to the applicable regulations at the school, thus enabling the development of the potential possessed by all students.